Key establishment for layered group-based Wireless Sensor Networks. (19th March 2010) - Li, Xueping; Yang, Dengfeng; Sawhney, Rapinder
Establishing pairwise keys for sensors is crucial to secure communications in Wireless Sensor Networks (WSNs). Several key pre-distribution schemes have been proposed to establish pairwise keys, but they are not scalable and suffer from a dramatic degradation of security when the number of compromised sensor exceeds a threshold. In this paper, we propose a Layered Group-based Key Establishment (LGKE) scheme, in which a logic top layer ensures the scalability through an Exclusion Basic System (EBS) technique while a logic low layer adopts a group-based key preload scheme to ensure the security. The security analysis and quantitative evaluation show the superiority of LGKE with regard to scalability, resilience, robustness and communication overhead.